Этносоциология: перспективы применения - Евтух, В. (Социология: теория, методы, маркетинг, 2000)
Despite the fact that this kind of research is rather new, ethno-sociology has proved to be efficient for solving problems connected with inter-ethnic relations. The sociological methods like questioning, interview, content-analysis etc. (for studying ethnic groups and other kinds of ethnic communities, their structures, self-realization mechanisms etc.) make it possible to reveal the most hurtful aspects of inter-ethnic relations,prevent conflict situations etc. Ethno-sociology deals with a series of dimensions which require inter-disciplinary approach within the frame of humanitarian sciences.